Significance and Outcome of Performing Upper GI Endoscopy and Colonoscopy for Paediatric GI Referrals (Medical Forum Monthly, 2024)
Objective: To diagnose treatable gastrointestinal diseases with help of upper GI endoscopy and colonoscopy.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Paediatric Gastroenterology, Hepatology & Nutrition, King Faisal Hospital & Research Centre, Jeddah, Kingdom of Saudi Arabia from March, 2016- September, 2016.Materials and Methods: Twenty children were recruited in this study with history of GI symptoms of chronic diarrhoea with and without blood, vomiting and abdominal pain. The referrals were made from small cities of Kingdom of Saudi Arabia to our tertiary centre.Results: Out of 20 referrals we were able to confirm 2 cases (10%) of coeliac disease, 5 cases (25%) of crohn’s disease, 3 cases (15%) of helicobacter pylori gastritis, 1 case (5%) of graft versus host disease (GVHD), 1 case (5%) of acute gastritis, 1 case (5%) of intestinal lymphangiectasia (IL), 4 cases (20%) of gastro-oesophageal reflux disease (GORD) and in 3 patients (15%) no pathology was found.Conclusion: We understand that clinicians at local level spent too much time before making these referrals. But by investigating them promptly especially with upper GI endoscopy and colonoscopy majority of them got diagnosed and managed appropriately.